2013
DOI: 10.1021/ja4079094
|View full text |Cite
|
Sign up to set email alerts
|

Bromine-Catalyzed Conversion of CO2 and Epoxides to Cyclic Carbonates under Continuous Flow Conditions

Abstract: A continuous method for the formation of cyclic carbonates from epoxides and carbon dioxide (CO2) is described. The catalysts used are inexpensive and effective in converting the reagents to the products in a residence time (t(R)) of 30 min. The cyclic carbonate products are obtained in good to excellent yield (51-92%). On the basis of a series of kinetics experiments, we propose a reaction mechanism involving epoxide activation by electrophilic bromine and CO2 activation by an amide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(64 citation statements)
references
References 50 publications
1
62
0
1
Order By: Relevance
“…However, the activity observed so far is not satisfactory and high CO2 pressure and temperature are still necessary. 16 It is suggested that surface hydroxy groups and/or Zn sites on solid catalysts act as Lewis acid sites, which may activate the epoxide then facilitate its ring opening.…”
mentioning
confidence: 99%
“…However, the activity observed so far is not satisfactory and high CO2 pressure and temperature are still necessary. 16 It is suggested that surface hydroxy groups and/or Zn sites on solid catalysts act as Lewis acid sites, which may activate the epoxide then facilitate its ring opening.…”
mentioning
confidence: 99%
“…From these results, a possible reaction mechanism using the cycloaddition of propylene oxide with CO 2 as an example is proposed and depicted in Scheme 3 based on the previous literatures [12,13,[34][35][36][37] and the observations in this reactions. At first, the substrate epoxide is activated by TiCl 5 -DMIL@SiO 2 @Fe 3 O 4 to form the complex 1 by the coordination of one TiCl 5 anion with O atom of propylene oxide.…”
Section: Resultsmentioning
confidence: 94%
“…However, these protocols suffered from some drawbacks such as the use of stoichiometric amount of catalysts and generation of vast amounts of corrosive wastes. In order to overcome these problems, many efforts have been developed for this transformation, and various catalysts have been developed including PS-TBMAC/ZnI 2 [6], salencomplexes [7][8][9][10][11], bromide [12], K 2 S 2 O 8 /NaBr [13], MOFs [14][15][16][17][18][19][20][21], quaternary ammonium hydroxide [22], supported imidazole [23], organocatalysts [24,25], and others [26][27][28][29]. However, some of these procedures still require Abstract A series of silica coated magnetic nanoparticles supported ILs were prepared, characterized and their catalytic performances in cycloaddition of CO 2 to epoxides were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Various organocatalysts and strategies for cyclic carbonate formation have been developed over the last ten years with different degrees of success when taking into account the overall sustainability of these processes (reaction conditions, reactivity, and the use of solvents). This work is exemplary for the majority of the organocatalytic promoters reported to date: compared to metal catalysts, the substrate activation potential is lower which results in much higher reaction temperatures that are required for FIGURE 8 Organocatalytic approaches toward cyclic carbonate synthesis [66][67][68][69]. The group of He reported on the use of polyethylene glycol (PEG) bridged basic ILs [66]: the key motif (see Figure 8) consists of an ethylene glycol that ties two quaternary 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD) units.…”
Section: Figurementioning
confidence: 99%
“…A rather original approach toward cyclic carbonate synthesis using organic molecules as mediators was described by Jamison and his group [69]. Combination of N-bromo-succinimide (NBS) with a radical initiator (benzoyl peroxide, BPO) in the presence of dimethylformamide (DMF) as medium in a continuous flow system allows for efficient conversion of epoxides and CO 2 into cyclic carbonates (conditions in Figure 8).…”
Section: Figurementioning
confidence: 99%